Illness Perceptions and Mortality in Patients With Gout: A Prospective Observational Study. Issue 9 (13th August 2017) - Serlachius, Anna; Gamble, Greg; House, Meaghan; Vincent, Zoe L.; Knight, Julie; Horne, Anne; Taylor, William J.; Petrie, Keith J.; Dalbeth, Nicola
Abstract : Objective: To examine whether illness perceptions independently predict mortality in early‐onset gout. Methods: Between December 2006 and January 2014, a total of 295 participants with early‐onset gout (<10 years) were recruited in Auckland and Wellington, New Zealand. The participants were followed up until February 2015, and mortality information was collected. Participants with complete data were included in the current study (n = 242). Cox proportional hazards models were used to examine the association between illness perceptions and mortality risk, after adjustment for covariates associated with disease severity and mortality in gout. Results: In a Cox proportional hazards model adjusted for predictors of disease severity and mortality in gout (number of tophi, serum urate level, and frequency of flares), consequence beliefs, identity beliefs, concern beliefs, and emotional response to gout were associated with all‐cause mortality (hazard ratios [HRs] 1.29, 1.15, 1.18, and 1.19, respectively; P  < 0.05 for all). In the fully saturated model, the association between consequence beliefs and mortality remained robust after additional adjustment for ethnicity, disease duration, diuretic use, serum creatinine, and pain score (HR 1.18 [95% confidence interval 1.02–1.37]; P  = 0.029). Conclusion: Negative beliefs about the impact of gout and severity of symptoms, as well as concerns about gout and the emotional response to gout, were independently associated with all‐cause mortality. Illness perceptions are important and potentially modifiable risk factors to target in future interventions.